A future for the Latino church : models for multilingual, multigenerational Hispanic congregations - Rodriguez, Daniel A., 1955- (Downers Grove, Ill. : IVP Academic, 2011)
Daniel Rodriguez argues that effective Latino ministry and church planting are now centered in second-generation, English-dominant leadership and congregations. Through careful study of dozens of cutting-edge Latino churches across the country, Rodriguez describes how innovative congregations are ministering creatively to the next generations of Latinos. In-depth case studies reveal how gifted leaders are reaching beyond their own demographics to have lasting impact on their wider communities. The future of the Latino church is multilingual, multigenerational and multiethnic. Those who "live in the hyphen" between Latino and American can become all things to Latinos, sharing the gospel where language is no barrier.
Introduction : a moment of transition in the barrio -- Living in the hyphen -- Multigenerational Hispanic churches -- Multiethnic, predominately Hispanic churches -- Good news and good works in the barrio -- The local church as organic seminary -- The new Hispanic challenge -- Conclusion : a future for the Latino church.
Includes bibliographical references (p. [184]-193) and indexes.
Keywords: Hispanic American churches